Overview of validated alternative methods for the detection of foodborne bacterial pathogens. (April 2017) - Rohde, Alexander; Hammerl, Jens Andre; Boone, Idesbald; Jansen, Wiebke; Fohler, Svenja; Klein, Günter; Dieckmann, Ralf; Al Dahouk, Sascha
Abstract: Background: Despite huge efforts to combat foodborne bacterial pathogens, the number of foodborne infections remains high throughout the world. Culture-dependent gold standard detection methods with their tedious and time-consuming procedures have approached their limits whereas the use of rapid and user-friendly alternative methods is on the rise. Validation by independent institutions, e.g. AOAC, AFNOR, MicroVal and NordVal, is a key element to demonstrate the applicability of a new method and its equivalence with standard procedures (e.g. DIN, ISO). Scope and approach: In this review, the suitability of currently available validated methods for the qualitative and quantitative bacteriological analysis of food is presented and discussed with special emphasis on the method-inherent strengths and weaknesses. Furthermore, an overview on general validation characteristics as well as further promising tools for the detection of foodborne pathogens is given. Key findings and conclusions: Improved cultivation methods as well as nucleic acid based and immunological methods dominate the market of alternative methods while emerging techniques like mass spectrometry, microarrays and phage-based techniques have yet to be thoroughly validated. Harmonized validation procedures are highly desirable as well as enhanced efforts to develop validated tests for a greater variety of pathogens, since current validated tests are mainly confined to the detection of Salmonella enterica and Listeria spp. Highlights: Gold standard methods for ensuring food safety have significant disadvantages. Alternative methods have to be thoroughly validated by independent institutions. Validated methods are dominated by molecular, immunological and cultural assays. Pathogen-specific testing concentrates on Salmonella and Listeria.